841 PAP Therapy Data Provides Clues To Comorbid Sleep Disorders. (3rd May 2021) - Bartley, Bethany; Cai, Alice; Epstein, Lawrence
Abstract: Introduction: Obstructive sleep apnea (OSA) is a common condition and positive airway pressure (PAP) therapy is the treatment of choice. Treatment guidelines recommend monitoring objective PAP usage data to track treatment efficacy. A typical report includes the percentage of days/month and cumulative hours/day a PAP device was used. In addition, PAP therapy timing can be graphically viewed with use plotted by time/day. This latter presentation reveals patterns of usage that can identify comorbid sleep disorders. Report of case(s): Case 1: A 65-year-old male with OSA presented with sleep inertia despite compliance with PAP therapy. Therapy timing data revealed a delayed circadian phase, with bedtime of 4 am and wake time of 1 pm. Circadian phase advancement therapy was added. Case 2: An 86-year-old male with OSA presented with daytime sleepiness after years of excellent PAP usage. Two years earlier, he was diagnosed with Parkinson's disease and developed increasing afternoon sleepiness. Compliance data showed a mild reduction in PAP usage. However, therapy timing data revealed an irregular sleep-wake rhythm disorder with sleep scattered around the clock, consistent with neurodegenerative disease. Case 3: A 70 year-old-female with PTSD and OSA presented with persistent tiredness and difficulty initiating and maintaining sleep despite good compliance with PAP therapy. Her timing data showed irregular sleep times with long gaps in usage suggestive of sleep maintenance insomnia. After starting a behavioral treatment regimen her pattern regularized and awakenings reduced, seen by consistent PAP use. Case 4: An 80-year-old female with OSA complained of early morning awakenings despite PAP use with good compliance. Review of PAP therapy timing revealed a pattern suggestive of advanced sleep-wake phase disorder. Circadian phase delay therapy was started. Conclusion: Patients with OSA on PAP therapy may have comorbid sleep disorders impacting sleep quality. PAP therapy data can provide information on sleep-wake behavior similar to actigraphy to help diagnose these conditions and track treatment response. Support (if any): None